Role of Focusing Distance in Picosecond Laser-Induced Cu Plasma Spectra - Chen, Linyu; Deng, Hu; Wu, Zhixiang; Xiong, Zhonggang; Guo, Jin; Liu, Quancheng; Samuel, Akwasi Danso; Shang, Liping (Advances in High Energy Physics, 2022)
To study the effects of focusing distance on the characteristics of copper plasma, a picosecond laser is utilized to ablate a pure copper plate to generate a plasma spectrum. Following numerous experiments on the subject, three significant factors are determined: lens focal length, pulse energy, and the lens-to-sample distance. These factors are employed to analyze the spectral intensity, plasma temperature, and electron density in the local thermodynamic equilibrium (LTE) and optically thin condition. Due to the shielding effects of mixed plasma, the strongest spectral intensity is achieved in the prefocused case, no matter how much beam irradiance is employed. The more intensive the beam irradiance is, the more the optimal position is distant from the focal point. The variation of plasma temperature and electron density showed a peak in the prefocused case, which is consistent with the trend of spectral intensity. For the case of extremely high irradiance (on the focus), the shielding effects become seriously, and the resultant above three factors decreased sharply. When a longer-focal-length lens is employed, the spectral intensity exhibited an obvious bimodal trend. In the prefocused case, a longer-focal-length lens is helpful to eliminate the effects of the roughness of the target surface compared with a shorter one. Finally, the assumed LTE is validated by McWhirter relation, plasma relaxation time, and diffusion length, and the optically thin condition was also validated by spectral intensity ratio. We hope that this work could be an important reference for the future design of highly optimized experiments for Calibration-Free Laser-Induced Breakdown Spectroscopy (CF-LIBS).